ANALYTICAL STUDY OF INDIAN VALUES ​​AND PHILOSOPHY EMBEDDED IN THE PREAMBLE OF THE INDIAN CONSTITUTION - Jaiswal, Rakesh Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The Preamble of the Indian Constitution is a concise description of the guiding principles and aspirations for the upliftment of the nation, encompassing a broad vision. This research paper delves deeply into the philosophical foundations underlying the Preamble of the Indian Constitution. This paper explores the Indian values ​​and ideals embodied in the Preamble and highlights their implications for the constitutional framework. Through an analysis of the historical context, the debates and philosophical influences of the Constitution makers at the time of the Constitution's creation, this research paper explores how the Preamble reflects the Indian values ​​and philosophical foundations of the Indian Constitution. It explores the philosophical foundations of the Preamble, including ideas of social justice and welfare, secularism and democratic governance. It highlights how these principles were shaped by the Indian National Movement, the influence of leaders such as Mahatma Gandhi, Jawaharlal Nehru and B.R. Ambedkar, as well as global thinkers such as Karl Marx and John Locke.